All is grace : a ragamuffin memoir - Manning, Brennan (David C. Cook, 2011)
Brennan Manning roves back through his past, honoring the lives of the people closest to him, family and friends who've known the saint and the sinner, the boy and the man. Far from some chronological timeline, these memories are witness to the truth of life by one who has lived it.